Patterns of cytokine release and association with new onset of post-cardiac surgery atrial fibrillation - Kota, Rahul; Gemelli, Marco; Dimagli, Arnaldo; Suleiman, Saadeh; Moscarelli, Marco; Dong, Tim; Angelini, Gianni D.; Fudulu, Daniel P. (Frontiers in Surgery, 2023)
Introduction: Postoperative Atrial Fibrillation (POAF) is a common complication of cardiac surgery, associated with increased mortality, stroke risk, cardiac failure and prolonged hospital stay. Our study aimed to assess the patterns of release of systemic cytokines in patients with and without POAF. Methods: A post-hoc analysis of the Remote Ischemic Preconditioning (RIPC) trial, including 121 patients (93 males and 28 females, mean age of 68 years old) who underwent isolated coronary artery bypass grafting (CABG) and aortic valve replacement (AVR). Mixed-effect models were used to analyze patterns of release of cytokines in POAF and non-AF patients. A logistic regression model was used to assess the effect of peak cytokine concentration (6 hours after the aortic cross-clamp release) alongside other clinical predictors on the development of POAF. Results: We found no significant difference in the patterns of release of IL-6 (P=0.52), IL-10 (P=0.39), IL-8 (P=0.20) and TNF-α (P=0.55) between POAF and non-AF patients. Also, we found no significant predictive value in peak concentrations of IL-6 (p=0.2), IL-8 (p = >0.9), IL-10 (p = >0.9) and Tumour Necrosis Factor Alpha (TNF-α)(p =0.6), however age and aortic cross-clamp time were significant predictors of POAF development across all models. Conclusions: Our study suggests no significant association exists between cytokine release patterns and the development of POAF. Age and Aortic Cross-clamp time were found to be significant predictors of POAF.